1990
DOI: 10.1144/gsl.eng.1990.006.01.28
|View full text |Cite
|
Sign up to set email alerts
|

Rock mass assessment from seismic measurements

Abstract: An important part of many site investigations is the geomechanical assessment of the rock mass in terms of a classification system which is independent of the user. All classification systems used to date are based on observation of the rock mass and the determination of simple engineering parameters on intact rock specimens. In this paper, the use of the seismic properties of the rock mass to assess the geomechanical performance of the rock mass are examined and illustrated by three case histories. It is show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
14
0
1

Year Published

1990
1990
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 10 publications
1
14
0
1
Order By: Relevance
“…The regression coefficients (r 2 ) of the three relationships (Table 3) are all above 0.7 for 256 points. The highest r 2 value is for the Log 10 regression line, which is plotted on (1965) and McCann et al (1990). The plot suggests that the sonic velocity may be used to find a limiting maximum strength.…”
Section: Resultsmentioning
confidence: 96%
See 3 more Smart Citations
“…The regression coefficients (r 2 ) of the three relationships (Table 3) are all above 0.7 for 256 points. The highest r 2 value is for the Log 10 regression line, which is plotted on (1965) and McCann et al (1990). The plot suggests that the sonic velocity may be used to find a limiting maximum strength.…”
Section: Resultsmentioning
confidence: 96%
“…discontinuities caused for example by fractures, jointing and infilled mineral veins, it can be used as a part of the assessment of the rock mass such as Rock Quality Designation (RQD) (Glenn & Nelson, 1979, McCann 1990. McCann et al (1981) introduced the concept of a simplified rock mass classification system based on the dynamic bulk modulus of the rock mass from sonic and shear velocity.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…D' Andrea et al (1965) compared the compressional wave velocities measured for a range of American rocks with their uniaxial compressive strengths. Whilst a correlation can be obtained, a similar comparison for a wider range of British rocks showed that a broad range of velocities can be obtained for weak rocks of fairly uniform strength and, conversely, for very strong rocks, velocity remains fairly constant despite large variations in strength values (McCann et al 1990). (1983) as one of the parameters for the determination of liquefaction potential.…”
Section: Vp Vpf Vp1mentioning
confidence: 92%